PREREQUISITES FOR THE APPLICATION OF MACHINE VISION IN GRAIN MATERIAL IDENTIFICATION - Stepanenko, Serhii; Dnes, Viktor; Shvydia, Viktor; Boris, Andriy; Kuzmych, Alvian (Collection of scientific papers «ΛΌГOΣ», 2024)
Ensuring Ukraine’s food security during martial law is one of the most pressing challenges in today’s agricultural production. Food grain remains a key source of nutrition globally. However, nearly 30% of the harvested crop is lost during harvesting and post-harvest processing. The use of non-destructive, timely, accurate, reliable, cost-effective, and environmentally safe methods for assessing grain quality has been a top priority for researchers and the agricultural industry in recent years [1-5].